Guidelines for Solid Waste Management Approaches at Kerng Sub-District Administrative Under the Maha Sarakham Provincial (Asian Journal of Social Science Studies, 2018)
To integrate the problems and needs of solid waste management (SWM) for administering the SWM approach at Kerng Sub-District Administrative Organization (K-SAO) under the Maha Sarakham PAO in Thailand were studied. This SAO increasingly shares in these problem natural limited products and highly vulnerable in 14 villages are arranged with a sample size of 357 people to their perceptions with the Questionnaire on Waste Management (QWM) and the Focus Group Discussion technique in three scales; Waste Collection, Waste Separation, and Waste Disposal scales, the classifications’ problems indicated that of moderate level. according to have their problems and needs, plastics bins are the type of their garbage bins, people collected the collecting SWM by the K-SAO, the households’ memberships have participated in the implementation of the project with social local communities, and took part in solving problems caused by the collection of the SWM on their communities, the K-SAO has been listening to comments of their suggestions and communities’ solving and given advices the burdensome problem of collecting waste to lack of responsibility. Most of guidelines the Waste Collection as to set at least twice a day and the public should be aware of the collection time and carry out their own fermentation. An importance campaign for people to sort out their sales from solid waste as Waste Separation scale was promoted. The Disposal Project Biomass Waste Treatment (MBT) was planned and organized to give pieces of advice for using disposal waste to relate waste collection time of the K-SAO was the guidelines.